2022
DOI: 10.1177/13623613221077721
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness in autistic adults: A systematic review

Abstract: In this systematic review, we examined quantitative, qualitative and mixed methods studies on loneliness in autistic adults. A total of 1460 articles were identified, and 34 of these met inclusion criteria. Results demonstrated that (1) there is a paucity of qualitative data providing first-hand descriptions of loneliness from autistic adults; (2) few empirical studies have used reliable/valid measures of loneliness developed specifically for autistic adults, and in just one study was a measure of loneliness d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 108 publications
2
22
0
Order By: Relevance
“…While autistic adults desire close relationships (Brownlow et al, 2015), many have difficulties initiating/maintaining relationships. They also experience challenges and discrimination in social and professional settings, which may contribute to the high rates of negative interactions and downstream negative mood (Orsmond et al, 2013;Umagami et al, 2022). It is important to provide ample opportunity to learn and practice I had a job lined up to move… next month to teach English as a Second Language, but due to the coronavirus, I will be remaining where I am until hopefully November.…”
Section: Discussionmentioning
confidence: 99%
“…While autistic adults desire close relationships (Brownlow et al, 2015), many have difficulties initiating/maintaining relationships. They also experience challenges and discrimination in social and professional settings, which may contribute to the high rates of negative interactions and downstream negative mood (Orsmond et al, 2013;Umagami et al, 2022). It is important to provide ample opportunity to learn and practice I had a job lined up to move… next month to teach English as a Second Language, but due to the coronavirus, I will be remaining where I am until hopefully November.…”
Section: Discussionmentioning
confidence: 99%
“…A deficit-based approach to understanding autism -together with the underestimation of the challenges autistic people face in their transition to adulthood -results in less access to social services and health assistance (Nicolaidis, Raymaker, McDonald, et al, 2013), lower employment rates (Hedley, Uljarević, & Hedley, 2017), lack of social networks and loneness (Umagami, Remington, Lloyd-Evans, Davies, & Crane, 2022). Adult autistic people struggle living independently, finding a job, or managing social interactions in the workplace when these social expectations are calibrated to neurotypical population (Marriage, Wolverton, & Marriage, 2009).…”
Section: Transition Into Adulthoodmentioning
confidence: 99%
“…12 In a recent systematic review, autistic adults were shown to report higher scores on measures of loneliness than a comparison group of nonautistic adults. 19 Loneliness ratings then associate with negative self-esteem, anxiety, depression, self-harm behaviours and suicidal ideation. [12][13][14] Autistic individuals report having fewer friendships and reduced quality of life specifically in relation to social relationships.…”
Section: Introductionmentioning
confidence: 99%